Cnemidophorus serranus - Arias, Federico José (2005)
CNEMIDOPHORUS SERRANUS. ARGENTINA: SANTIAGO DEL ESTERO: Parque Nacional Copo, in an old growth forest(25°39'45.5"S; 61°47'50.10"). 13 December 2002. F. Lobo and I.Martinez Oliver. Verified by J. M. Diaz Gomez. Museo de CienciasNaturales, Universidad Nacional de Salta, Salta, Argentina (MCN1150). Previously known from Sierras de Cordoba and Ambargastain Santiago del Estero province (Cei 1993. Reptiles del Noroeste,Nordeste y Este de la Argentina. Mus. reg. Sci. nat. Torino, Monogr.14: 949 pp.). Present record extends range ca. 500 km N fromAmbargasta, Santiago del Estero the nearest locality known (Ceiand Martori 1991. Boll. Mus. Reg. Sci. Nat. Torino 9[1]:33-38).